Estrogen modulation properties of mangiferin and quercetin and the mangiferin metabolite norathyriol. Issue 6 (10th June 2015) - Wilkinson, Ashley S.; Taing, Meng-Wong; Pierson, Jean Thomas; Lin, Chun-Nam; Dietzgen, Ralf G.; Shaw, P. Nicholas; Gidley, Michael J.; Monteith, Gregory R.; Roberts-Thomson, Sarah J.
<x xml:space="preserve">Abstract</x> Mango fruit contain many bioactive compounds, some of which are transcription factor regulators.